Dual Symmetric Multiple-mode Resonators (MMRs) Designed with Defective Ground Structure for UWB Applications - Dayang Azra, Awang Mat; Lee, Yee Hui; Dyg Norkhairunnisa, Abang Zaidel (2022)
This research paper discussed on the design of UWB-BPF with defected ground structure for microwave applications. The designed UWB-BPF is made up of four meandered line type of defective ground structures and dual symmetric multiple-mode resonators (DSMMRs). Rogers RO4003C substrate is used to fabricate the proposed design BPF which have a relative permittivity, Ɛr of 3.38 and R&S Vector Network Analyzer is used for the measurement of the Fabricated BFP. As a result, passband performance and skirt selectivity were improved. The proposed BPF has a passband frequency range of 3.0-10.6GHz and the size of the UWB-BPF is approximately 21.6mm ×30 mm.